Penerapan Kafa’ah dalam Perkawinan menurut Fiqh Al- Syāfi’iyyah: (Studi Kasus di Gampong Cebrek Kec Kembang Tanjong Kab Pidie) - Rahmadani, Suci; Afrizal; Ula, Multazimah; Aprilla, Maya (Yayasan Madinah Al-Aziziyah, 2024)
This study focuses on the application of kafa’ah (equality) in marriage in Gampong Cebrek, Kembang Tanjong District, Pidie Regency, and its evaluation according to Fiqh Al-Syāfi’iyyah. Recent trends show that society tends to prioritize social status and wealth over ensuring kafa’ah between spouses. Although some individuals understand the importance of equality, many neglect this concept due to limited religious knowledge. This research employs a qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that kafa’ah is not fully practiced in the local community. Limited religious understanding contributes to the lack of awareness about the significance of kafa’ah in marriage. From the perspective of Fiqh Al-Syāfi’iyyah, the practice of kafa’ah in Gampong Cebrek aligns with the teachings outlined in the Fiqh Al-Syāfi’iyyah texts, although further improvements are needed in its application within the community.